Condutividade elétrica massal e individual para determinação do potencial fisiológico de sementes de milho - Vidal, Maquiel Duarte (2010)
The objective of this work was to study the execution of the conductivity test in embryo of maize seeds. Were used five lots of maize seeds, Pioneer 32R48 hybrid cultivar. The seeds were submitted to a set of tests in order to measure the physiological potential: moisture content, germination, first count germination, cold test (without soil), evaluation of seedlings, electrical conductivity, seedlings emergency in the field and evaluation of epicotyls of emergency. After this, was realized the electrical conductivity in embryos, were used ten embryos imbibed in 40 mL of deionized water, for 30 minutes to 25ºC. For extraction of embryo the seeds were soaking for 18 hours to 25ºC, in absence of light. The results showing that, embryos of lots of low physiologic potential leachate more amount of ions in the soaking water than lots of high physiologic potential so, it can be concluded that the electrical conductivity test, realized exclusively in maize embryo, using ten embryos imbibed in 40 mL of deionized water for 30 minutes to 25ºC, is capable determine the lots quality, and more efficient than conventional methods that using integrals seeds.